Complex Plasma Research under Microgravity Conditions: PK‐3 Plus Laboratory on the International Space Station. Issue 3 (24th February 2016) - Khrapak, A. G.; Molotkov, V. I.; Lipaev, A. M.; Zhukhovitskii, D. I.; Naumkin, V. N.; Fortov, V. E.; Petrov, O. F.; Thomas, H. M.; Khrapak, S. A.; Huber, P.; Ivlev, A.; Morfill, G.
Abstract: Complex (dusty) plasmas are composed of weakly ionised gas and charged microparticles and represent the plasma state of soft matter. Due to the "heavy" component – the microparticles – and the low density of the surrounding medium, the rarefied gas and plasma, it is necessary to perform experiments under microgravity conditions to cover a broad range of experimental parameters which are not available on ground. The investigations have been performed onboard the International Space Station (ISS) with the help of the "Plasma Crystal‐3 Plus" (PK‐3 Plus) laboratory. It was perfectly suited for the formation of large stable liquid and crystalline systems and provided interesting insights into processes like crystallisation and melting, laning in binary mixtures, electrorheological effects due to ac electric fields and projectile interaction with a strongly coupled complex plasma cloud. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)